ANALISIS AKUNTANSI PAJAK PENGHASILAN BADAN PADA CV. KARYA NATAL - Fitriani Saragih (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
ABSTRACTThis study aimed to determine the corporate income tax accounting which is conducted by CV. Karya Natal. This study using descriptive analysis method. The data used in this study came from the secondary data that in the form of Income Statement and Annual Tax Return for the year 2013, 2014 and 2015. The results obtained in this study that the corporate income tax accounting has not been applied properly because the calculations that made by company is not accordance with Law Number 36 of 2008.Keywords : Tax Accounting, Corporate Income Tax, Income Statement